Non-destructive imaging of buried electronic interfaces using a decelerated scanning electron beam - Atsufumi Hirohata (Nature Portfolio, 2016)
Imaging buried interfaces is necessary to assess the quality of electronic devices and their degradation mechanisms. Here, Hirohata et al. use energy-filtered scanning electron microscopy to image buried defects in an inorganic lateral spin-valve device, at the nanometre scale and non-destructively.